HATE SPEECH ON ROCKY GERUNG OFFICIAL YOUTUBE CHANNEL AGAINST PRESIDENT JOKO WIDODO: A PRAGMATIC STUDY - Wulandari S. (International Journal of Social Science, 2022)
This study aims to reveal two things, namely the forms of hate speech on the Rocky Gerung Official youtube channel against President Joko Widodo and the forms of illocutionary speech acts in hate speech on the Rocky Gerung Official youtube channel against President Joko Widodo. This type of research is qualitative research with a pragmatic approach. The method used in this study, namely the method of listening to the technique of documentation and note-taking techniques. The data sources for this research are videos on the Rocky Gerung Official youtube channel in 2021-2022. The population of this research is the entire speech containing hate speech on the Rocky Gerung youtube channel. Sampling was done purposively. The data analysis of this research was done descriptively. The results of this study indicate that on the Rocky Gerung Official youtube channel there are six forms of hate speech against President Joko Widodo, namely insults, defamation, unpleasant acts, provocation, incitement, and spreading of false news and there are four forms of illocutionary speech acts in hate speech. Towards President Joko Widodo in the form of assertive, expressive, commissive, and declarative with each function, namely, stating, informing, promising, angry, feeling funny, and giving names